Fusobacterium nucleatum Accelerates Atherosclerosis via Macrophage-Driven Aberrant Proinflammatory Response and Lipid Metabolism - Zhou, Jieyu; Liu, Lin; Wu, Peiyao; Zhao, Lei; Wu, Yafei (Frontiers in Microbiology, 2022)
Periodontitis, an oral chronic inflammatory disease, is reported to show an association with atherosclerotic vascular disease (ASVD). Fusobacterium nucleatum, is an oral commensal bacterium and abundantly implicated in various forms of periodontal diseases. however, its role in the pathogenesis of atherosclerosis is unclear. This study aimed to elucidate the underlying pathogenic mechanisms of atherosclerosis induced by F. nucleatum to provide new insight on the prevention and treatment of atherosclerosis. We used an animal model, that is, ApoE−/− mice were infected with F. nucleatum by oral gavage, and in vitro co-culture models to assess the pathogenicity of F. nucleatum. The results indicated that F. nucleatum ATCC 25586 invaded aortic tissues and substantially increased the progression of atherosclerotic lesions. In addition, F. nucleatum changed plaque composition into a less-stable phenotype, characterized with increased subcutaneous macrophage infiltration, M1 polarization, lipid deposition, and cell apoptosis, and reduced extracellular matrix and collagen content. The serum levels of pro-atherosclerotic factors such as interleukin (IL)-6, IL-1β, tumor necrosis factor (TNF)-α, monocyte chemoattractant protein-1 (MCP-1), c-reactive protein (CRP), and oxidized low-density lipoprotein (ox-LDL) and microRNAs (miR-146a, miR-155, and miR-23b) were considerably increased by F. nucleatum stimulation, whereas HDL-c level was reduced. F. nucleatum induced in-vitro macrophage apoptosis in a time- and dose-dependent manner. F. nucleatum facilitated ox-LDL-induced cholesterol phagocytosis and accumulation by regulating the expression of lipid metabolism-related genes (AR-A1, ACAT1, ABCA1, and ABCG1). F. nucleatum further worsens the atherosclerotic plaque microenvironment by considerably increasing the levels of IL-6, IL-1β, TNF-α, MCP-1, and MMP-2, 8, and 9 and by suppressing fibronectin (FN) 1 level during foam cell formation. This study showed that F. nucleatum ATCC 25586 is implicated in atherosclerosis by causing aberrant activation and lipid metabolism in macrophage.